Homo‐ and Heterodinuclear Iron Clathrochelate Complexes with Functional Groups in the Ligand Periphery. Issue 26 (23rd April 2018) - Bila, José L.; Marmier, Mathieu; Zhurov, Konstantin O.; Scopelliti, Rosario; Živković, Ivica; Rønnow, Henrik M.; Shaik, Noore E.; Sienkiewicz, Andrzej; Fink, Cornel; Severin, Kay
Abstract : Dinuclear iron clathrochelate complexes were prepared by metal‐templated condensation reactions of 4‐pyridylboronic acid and phenol dioximes in the presence of Fe III and/or Fe II salts. The complexes are accessible in two distinct redox states, featuring either two Fe II centers or a mixed‐valence Fe II /Fe III state. It is possible to reversibly switch between the two forms by chemical oxidation/reduction or electrochemically. A heterometallic Zn II /Fe III clathrochelate was obtained by using a mixture of zinc and iron salts. All complexes feature terminal pyridyl groups, which makes them interesting building blocks for metallosupramolecular chemistry. Metal ion exchange reactions indicate that the iron clathrochelate complexes are thermodynamically more stable than the analogous zinc and cobalt complexes. The high stability allowed to prepare a clathrochelate polymer by palladium‐catalyzed polycross‐coupling of a polybrominated clathrochelate complex with 1, 4‐benzenediboronic acid. The polymer network displays permanent porosity with an apparent Brunauer–Emmett–Teller surface area of SA BET = 510 m 2  g –1 . The polymer is thermally stable and not susceptible to hydrolytic degradation. Abstract : Dinuclear iron clathrochelate complexes are described. The easy‐to‐access complexes are redox‐active, robust, and they can be decorated with functional groups. These properties make them interesting building blocks for supramolecular chemistry and materials science.